Code of West Virginia Comprising Legislation to the Year 1870, ch. 148, p. 692 - (:unkn) unknown (My University, 1868)
Prohibited habitually carrying concealed any pistol, dirk, Bowie-knife, or weapon of the like kind. Violators fined fifty dollars.
Keywords: CARRY - CONCEALED